A qualitative investigation of patients' understanding of carbohydrate in the clinical management of type 2 diabetes. Issue 2 (26th January 2015) - Breen, C.; McKenzie, K.; Yoder, R.; Ryan, M.; Gibney, M. J.; O'Shea, D.
Abstract: Background: A healthy diet is the cornerstone of type 2 diabetes (T2DM) self‐management. Carbohydrate is of particular interest as the nutrient with the greatest direct effect on blood glucose (BG) levels. The present study aimed to explore T2DM patients' understanding of carbohydrate and beliefs around the role of carbohydrate in T2DM management. Methods: Fifteen semi‐structured interviews were conducted with T2DM patients. Interviews were audio‐recorded and transcribed, and a deductive thematic approach to analysis was employed using the Framework method. Results: Four significant themes emerged: (i) a naïve conceptual understanding of carbohydrate and sugar‐centric specificity to dietary behaviours; (ii) a narrow focus on BG management to the neglect of overall dietary balance; (iii) positive reception of moderate dietary advice focused on portion control from healthcare professionals (HCPs); and (iv) the impact of external moderators of dietary choices, including the influence of significant others, emotional and opportunistic eating and budgetary constraints. Conclusions: Participants' beliefs and understanding of carbohydrate led to an overemphasis on sugar restriction for blood glucose control to the neglect of their overall dietary balance. Diabetes educators need to place greater emphasis on the role of various types of carbohydrate foods for glycaemic control, as well as on concepts of wider metabolic health, during T2DM dietary education. Participants placed a high level of trust and value on practical, moderate portion control advice from HCPs regarding carbohydrate foods. However, HCPs need to be cognisant of external moderators of behaviour, such as the influence of family and friends, budgetary constraints and environmental eating triggers.